2023
DOI: 10.3390/colorants2010004
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive On-Site pXRF Analysis of Coloring Agents of Under- and Over-Glazes: Variability and Representativity of Measurements on Porcelain

Abstract: The study of rare objects requires the use of mobile non-invasive methods such as a portable X-ray fluorescence instrument (pXRF), but this involves an analysis from the outer surface, while the depth analyzed depends on the element measured and, in addition, the material can be very heterogeneous at different scales. The concept of elemental composition, therefore, has no “absolute” meaning for painted enamel decorations. This work evaluates this concept by comparing the pXRF measurements made with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…It is necessary to consider the relative intensity of Fe Kα/Kβ and the width of Fe Kβ line to visually detect cobalt in small quantities. It is the same for the superposition of Pb Lα and As Kα, only As Kβ is visible just below Pb Lβ line[23][24][25]39,40]. Slight surface pollution on the entire surface of the porcelain during overglaze firing is detectable, as for the MNC 2274.9 bowl, due to the large sensitivity of XRF analysis in the detection of lead.…”
mentioning
confidence: 76%
“…It is necessary to consider the relative intensity of Fe Kα/Kβ and the width of Fe Kβ line to visually detect cobalt in small quantities. It is the same for the superposition of Pb Lα and As Kα, only As Kβ is visible just below Pb Lβ line[23][24][25]39,40]. Slight surface pollution on the entire surface of the porcelain during overglaze firing is detectable, as for the MNC 2274.9 bowl, due to the large sensitivity of XRF analysis in the detection of lead.…”
mentioning
confidence: 76%
“…In addition, the determination of a concentration %wt (which can be done by the ARTAX software) does not make sense because the enamel decoration is very heterogeneous (superposition of layers of variable thickness between a few tens and hundreds of µm containing variable distributions of pigments and coloring agent). This problem has been discussed in previous works [15,16,69] and the repeatability measurements on reference shards showed that the variability was primarily a function of the intrinsic multi-scale heterogeneity (from micron to cm) of the painted decorations [70]. The data fitting procedure has been already used in previous papers [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…The 16th century Ottoman artefacts use preferentially the chromite type like the Safavid productions. A previous study on the variability of elementary composition information on the same shard [91] makes it possible to estimate that for example the two subgroups observed in Figure 12b for Safavid tablewares are significant. Consequently, for example, for the ternary diagram of Figure 12a at least 7 subgroups are identifiable for the black lines and 5 for the colour brown.…”
Section: Black Linesmentioning
confidence: 96%